Evaluasi Mutu Pelayanan Apotek Dalam Pelayanan Kefarmasian Apotek Riyad di Surakarta Periode Desember 2022 - Safitri, Yuli; Anggraini, Truly Dian (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
According to the Regulation of the Minister of Health of the Republic of Indonesia Number 73 of 2016, the quality of pharmaceutical services in pharmacies can be guaranteed through the use of pharmaceutical service standards. Quality pharmaceutical services have an influence as far as customers are satisfied and there are no complaints about the services provided at the pharmacy. Problems that emerged at the Riyad Pharmacy during January to September 2022 included the lack of friendliness of pharmacy staff in serving visitors, prescription drug service taking a long time and limited drug stock. Using the Community Satisfaction Index (IKM) questionnaire, this research aims to measure satisfaction with pharmacy services from the aspects of responsiveness, reliability, assurance, empathy, and concrete evidence of the quality of pharmaceutical services at the Riyad Surakarta Pharmacy. The quality of pharmaceutical services offered by Apotek Riyad Surakarta was evaluated and the results were described using descriptive research methods. Purposive sampling was used to select 210 pharmaceutical service users for this study. The Community Satisfaction Index (IKM) score at Riyad Surakarta Pharmacy is 78 with service quality B including good service performance, according to a study of pharmaceutical service quality.